New Approaches for Security, Privacy and Trust in Complex Environments c - Venter, Hein.; Eloff, Mariki; Labuschagne, Les.; Eloff, Jan.; Solms, Rossouw von.; SpringerLink (Online service) (Boston, MA : Springer US, 2007)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of referred international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springer.com. For more information about IFIP, please visit www.ifip.org.
Digital Forensics -- FORSIGS: Forensic Signature Analysis of the Hard Drive for Multimedia File Fingerprints -- Digital Forensic Readiness as a Component of Information Security Best Practice -- Human-Computer Interaction I -- Value creation and Return On Security Investments (ROSI) -- Usability and Security of Personal Firewalls -- Computer-Based Trust -- Trusted Ticket Systems and Applications -- Trust Evaluation for Web Applications based on Behavioral Analysis -- Information Security Management I -- Improving the Information Security Model by using TFI -- Ontological Mapping of Common Criteria$1 (Bs Security Assurance Requirements -- Network Security I -- Management of Exceptions on Access Control Policies -- Security Analysis of Two Ultra-Lightweight RFID Authentication Protocols -- Information Security Management II -- Exploratory survey on an Evaluation Model for a Sense of Security -- Employees$1 (BAdherence to Information Security Policies: An Empirical Study -- Network Security II -- Phishing in the Wireless: Implementation and Analysis -- Secure Path-Key Revocation for Symmetric Key Pre-distribution Schemes in Sensor Networks -- Access Control I -- A Credential-Based System for the Anonymous Delegation of Rights -- Development and Application of a Proxy Server for Transparently, Digitally Signing E-Learning Content -- Human-Computer Interaction II -- Identity Theft $1 (BEmpirical evidence from a Phishing Exercise -- A Practical Usability Evaluation of Security Features in End-User Applications -- Intrusion Detection Systems -- Personal Anomaly-based Intrusion Detection Smart Card Using Behavioural Analysis -- A Survey of Bots Used for Distributed Denial of Service Attacks -- Access Control II -- A Hybrid PKI-IBC Based Ephemerizer System -- Keystroke Analysis for Thumb-based Keyboards on Mobile Devices -- Information Privacy I -- Security Remarks on a Convertible Nominative Signature Scheme -- Using Payment Gateways to Maintain Privacy in Secure Electronic Transactions -- Access Control III -- A Role-Based Architecture for Seamless Identity Management and Effective Task Separation -- Extending Role Based Access Control Model for Distributed Multidomain Applications -- Information Privacy II -- A Middleware Architecture for Integrating Privacy Preferences and Location Accuracy -- Enabling Privacy of Real-Life LBS -- Access Control IV -- Crafting Web Counters into Covert Channels -- OPA: Onion Policy Administration Model $1 (BAnother approach to manage rights in DRM -- Security Services -- Non-Repudiation in Internet Telephony -- FirePatch: Secure and Time-Critical Dissemination of Software Patches -- Access Control V -- An Experimental Evaluation of Multi-Key Strategies for Data Outsourcing -- Building a Distributed Semantic-aware Security Architecture -- Trust and Intrusion Detection Systems -- Using Trust to Resist Censorship in the Presence of Collusion -- Evaluating the Effects of Model Generalization on Intrusion Detection Performance -- Keynote paper -- Modernising MAC: New Forms for Mandatory Access Control in an Era of DRM -- IFIP WG 9.7/11.7 $1 (BIT Missue and the Law & the NoE (3z(BFuture of Identity in the Information Society(3y (B(FIDIS) $1 (BWorkshop on Security and Control of Identity in Society -- Covert Identity Information in Direct Anonymous Attestation (DAA) -- Safeguarding Personal Data using Rights Management in Distributed Applications -- Identification Now and in the Future: Social Grant Distribution Process in South Africa -- Hard-drive Disposal and Identity Fraud -- An analysis of security and privacy issues relating to RFID enabled ePassports -- IFIF WG 11.1/11.8 Workshop on Fostering Knowledge and Skills for Managable Information Security -- Toward User Evaluation of IT Security Certification Schemes: A Preliminary Framework -- Teaching of Information Security in the (3z(BHealth Care and Nursing(3y (BPostgraduate program -- Remote Virtual Information Assurance Network -- Certifying the Computer Security Professional Using the Project Management Institute$1 (Bs PMP Model.s
Keywords: Computer science; Computer security; Data encryption (Computer science).; Computer Science; Data Encryption; Systems and Data Security; Electronic books